Knowledge, awareness and attitude of needle stick and sharp injuries among allied medical science students of a tertiary care centre - ARCHANA NAGARAJAN; M.KALYANI; S.S.M UMAMAGESWARI; NEELU SREE (International Journal of Pharma and Bio Sciences, 2017)
Blood borne pathogenic micro-organisms are transmitted to healthcare workers through needle stick and sharp injuries (NSSI), and these contribute an important occupational hazard. To assess the knowledge, awareness and attitude of needle stick and sharp injuries (NSSI) among allied medical science students in a tertiary care centre. A cross-sectional study was conducted among allied medical students. A pre-test and post-test questionnaire, were used to assess the knowledge, awareness and attitude of NSSI. Data were analyzed statistically. All the 100 nursing, 110 Allied Health Sciences (AHS) and 25 medical laboratory technician (MLT) students participated. The median age was 18 years and the male to female ratio was 1:4. Even though all these students had previous diploma in nursing qualification, the pre-test revealed that their knowledge, awareness and attitude on NSSI were suboptimal. In this study, the students had suboptimal level of knowledge regarding the occurrence and prevention of NSSI before pre-test. After post-test significant improvement was noticed. Completion of Hepatitis B vaccination should be ascertained and completed in the beginning of various health care professional courses. Role play and small group were considered to be the better way to improve their understanding and attitude towards prevention and management of NSSI.